Comparison of the performance of waste leachate treatment in submerged and recirculated membrane bioreactors. (August 2015) - Xue, Yiting; Zhao, Huihui; Ge, Lin; Chen, Zheng; Dang, Yan; Sun, Dezhi
Abstract: The performances of a submerged and a recirculated membrane bioreactor (MBR) were compared for processing of fresh leachate, treated by an expanded granular sludge bed (EGSB)-anoxic/two-stage aerobic moving bed biofilm reactor (MBBR) system. The submerged membrane bioreactor (S-MBR) was operated at a constant permeate flux and the recirculated membrane bioreactor (R-MBR) at a constant transmembrane pressure (TMP). In both reactors, the removal efficiency of COD reached more than 93% and that of NH 4 + − N more than 97% in 100 days of operation. Long-chain alkanes, sulfur and protein-like substances in the influent could be removed by both the submerged and recirculated reactors. The frequency of cleaning of the R-MBR (5 times) was less than that of the S-MBR (7 times) in 100 days of operation. The fouling rate of the R-MBR was lower than that of the S-MBR. The inference is that the R-MBR is more appropriate for treating large amounts of wastewater than the S-MBR, which is more susceptible to membrane fouling by leachate. The study of the membrane fouling mechanism suggests that the cake layers of both reactors consisted largely of inorganic matter, i.e., CaCO3, polysaccharides and proteins. High-throughput sequencing results showed the bacteria in the cake layer to be mainly Proteobacteria and Bacteroidetes . The cake layer of the R-MBR had greater bacteria community diversity than the S-MBR. Highlights: Performance comparison of waste leachate treatment with two types of MBRs. Mechanism study of membrane fouling of two MBRs. Microbial community analyses in cake layers by high-throughput sequencing.